DEVELOPMENT OF GASTROPATHY AGAINST THE BACKGROUND OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN PATIENTS WITH RHEUMATOID ARTHRITIS AGAINST THE BACKGROUND OF VIRULENT GENES OF HELICOBACTER PYLORI (World Bulletin of Public Health, 2025)
The article provides data on the result of a molecular genetic study of the genotypic characteristics of Helicobacter pylori in the formation of NSAIDs of gastropathy in patients with rheumatoid arthritis.
Keywords: rheumatoid arthritis; gastropathies; pcr